Review Of the Effectiveness and Implementation of The Unified Periodic Tax Return (Coretax) On Government Agency Taxpayer Compliance and Tax Revenue at Tax Office X - Naufal Satria Daniswara; Asqolani Asqolani (Polytechnic of State Finance STAN, 2025)
This study examines the effectiveness and implementation of the Unification Periodic Tax Return within the Coretax system on the compliance of government agency taxpayers and tax revenue at tax office X. This study employs a qualitative method with data collection techniques through in-depth interviews with Account Representatives and representatives of government agency taxpayers, as well as documentation studies. The results indicate that the Coretax implementation created a